Board Diversity, Ukuran Perusahaan, Tax Aggressiveness, dan Kepemilikan Institusional terhadap Kualitas Laba - Andreas Bambang Daryatno; Linda Santioso (Jurnal Bisnis dan Akuntansi, 2021)
The research aims to provide empirical evidence on board diversity, firm size, tax aggressiveness, and institutional ownership of earnings quality in manufacturing companies listed on the Indonesian stock exchange, especially in 2016-2018. The study population is manufacturing companies listed on the Indonesia Stock Exchange. The sample selection method used in this study is nonprobability sampling with purposive sampling technique. The analysis method used is panel data regression. The results showed that board diversity has an effect on earnings quality. Meanwhile, firm size, tax aggressiveness, and institutional ownership do not affect earnings quality.